AN INCLUSIVE SETTING FOR HIGH FUNCTIONING AUTISM SPECTRUM DISORDER (HFASD) IN HOSPITALITY COURSE: A REVIEW - Wan Nurfarihin Wan Zamri; Norfezah Binti Md Nor (Journal of Islamic, Social, Economics and Development, 2023)
Higher education institutions are enrolling more students with autism spectrum disorder (ASD), and these individuals' fresh experiences and available assistance have an influence on their performance there. For better understanding on supporting system available for students with autism spectrum disorder, scoping review were conducted based on guided research question. Few steps of systematic searching strategy in identifying reliable existing article, reviewing, identifying gaps and recommended future research. Three trusted academic databases been used in finding relevant literature (Scopus, Science direct, and Google Scholar). Out of 195 screened studies, only 8 were accepted which met the inclusion criteria of study. Autism support system are found to be classified into three theme which is 1) Emotional Support System 2) Academic Support System 3) Environmental Support System. This outcome particularly found to minimize level of stress and anxiety due to stigma and misconception of community.